Salutogenesis and Coping Ways to Overcome Stress and Conflicts - Braun-Lewensohn, Orna; Mayer, Claude-Helene (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume of Proceedings gathers papers presented at XOVETIC2020 (A Coruña, Spain, 8-9 October 2020), a conference with the main goal of bringing together young researchers working in big data, artificial intelligence, Internet of Things, HPC (High-performance computing), cybersecurity, bioinformatics, natural language processing, 5G, and other areas from the field of ICT (Information Communications Technology); and offering a platform to present the results of their research to a national audience in Portugal. This third edition aims to serve as the basis of this event, which will be consolidated over time and acquire international projection.